2015 International Conference on Advances in Computing, Communications and Informatics (ICACCI) 2015
DOI: 10.1109/icacci.2015.7275751
|View full text |Cite
|
Sign up to set email alerts
|

Classification and clustering for neuroinformatics: Assessing the efficacy on reverse-mapped NeuroNLP data using standard ML techniques

Abstract: NeuroinformaticsNatural LanguageProcessing (NeuroNLP) relies on clustering and classification for information categorization of biologically relevant extraction targets and for interconnections to knowledge-related patterns in event and text mined datasets. The accuracy of machine learning algorithms depended on quality of text-mined data while efficacy relied on the context of the choice of techniques. Although developments of automated keyword extraction methods have made differences in the quality of data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Since computational cost was increased due to clustering and mapping, the runtime efficiency was increased by saving query results in a local database and retrieving non-listed documents based on the search results. Mapping cluster labels to MeSH terms helped to avoid irrelevant cluster labels and improved machine learning accuracy [36]. By using different machine learning algorithms, it was found that reverse mapped data showed higher accuracy compared to data extracted directly from retrieved documents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since computational cost was increased due to clustering and mapping, the runtime efficiency was increased by saving query results in a local database and retrieving non-listed documents based on the search results. Mapping cluster labels to MeSH terms helped to avoid irrelevant cluster labels and improved machine learning accuracy [36]. By using different machine learning algorithms, it was found that reverse mapped data showed higher accuracy compared to data extracted directly from retrieved documents.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning has been used in addressing BioNLP aspects including text classification [32], tagging structured models [33], parsing and extraction [34], and unsupervised learning with structure induction and document clustering [35]. In a previous study [36], performance of several machine learning algorithms on BioNLP datasets was evaluated. Eight classifiers-based learning models on 2000-point dataset with MeSH terms as features showed ~78.2% training accuracy, while the root mean square error was <0.26.…”
Section: Machine Learning and Natural Language Processingmentioning
confidence: 99%
See 1 more Smart Citation